DDRE-32. SETD2 HISTONE METHYLTRANSFERASE MUTATION STATUS PREDICTS TREATMENT RESPONSE IN GLIOBLASTOMA: STRATEGIES TO OVERCOME CHEMORESISTANCE. (12th November 2021) - Goldstein, Michael; Gabriel, Nishanth; Inkman, Matthew; Zhang, Jin; Dahiya, Sonika
Abstract: A major challenge in GBM treatment is tumor resistance to radiation and chemotherapy. A hallmark of GBM is the frequent mutation of epigenetic modifiers resulting in alteration of epigenetic signaling pathways. However, the effect of epigenetic signaling on chemotherapy response in GBM remains unknown. SETD2 is a histone methyl transferase that facilitates H3K36 tri-methylation. Here, we unveil the role of SETD2 mutations that frequently occur in GBM in tumor resistance to temozolomide chemotherapy. Targeted sequencing of the SETD2 gene in GBM tumor samples revealed that SETD2 mutations are associated with reduced overall survival in patients with methylated MGMT (methyl-guanine methyl transferase) promotor who received temozolomide. Consequently, we demonstrate that loss of SETD2 results in reduced H3K36me3 levels and a profound temozolomide resistance in GBM cells. MGMT-deficient tumors can acquire chemoresistance due to disrupted mismatch repair (MMR), a DNA repair pathway that converts primary temozolomide-induced DNA lesions into toxic DNA double-strand breaks. Strikingly, we found that SETD2 loss abrogates the expression of the MMR factor MSH6 indicating that chemoresistance in SETD2-deficient cells us due to disrupted MMR. Mechanistically, we show that SETD2 regulates MMR by promoting transcription of the MSH6 gene in GBM. Epigenetic modifiers have specific antagonists capable of reversing chromatin alterations induced by these modifiers. This provides a unique opportunity to restore chemotherapy response in SETD2-mutant GBM by targeting the antagonists of SETD2. We demonstrate that combined targeting of H3K36me3-specific histone de-methylases KDM4A and NO66 restores H3K36me3 levels along with MSH6 expression and sensitivity to temozolomide in SETD2-deficient GBM cells. Thus, our findings establish SETD2 mutation as a novel molecular marker predictive of chemotherapy response in GBM and provide a framework for a novel approach to overcome chemotherapy resistance in this malignant brain tumor by targeting an epigenetic pathway.